(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Indrayani, Putra RP, Hambali A, Ardiansyah. 2022. Isolation and characterization of extremophile bacteria for hydrolytic enzyme production from Waepella Hot Spring, Sinjai, Indonesia. Biodiversitas 23: 6345-6351. Extremophiles are organisms that have adapted to live in extreme environments. Therefore, they have huge potential for various industrial applications, specifically enzyme production. The aim of this study was to isolate and screen the potential of extremophile bacteria for hydrolytic enzyme production from the Waepella hot spring in Sinjai District, South Sulawesi, Indonesia. The water samples were collected from the hot spring at three different locations. The method of bacterial isolation was the agar plating technique using Tryptic Soy Agar media. The obtained isolates were characterized by examination of colony colors, cell shapes, gram staining, endospore, catalase, and enzymatic activity (amylase, cellulose, protease, lipase, and pectinase). The result showed that a total of eighteen isolates were successfully isolated from Waepella hot springs. Eight isolates showed amylolytic activity, and the highest (22.6± 0.44 mm) activity was observed in isolate BHSS10. Nine isolates had a cellulolytic activity with the highest clear zone of 11.6±0.4 mm (isolate BHSS7). Sixteen isolates had a pectinolytic activity with the highest clear zone of 12±0.24 (isolate BHSS16). Only 3 isolates showed proteolytic activity, and the highest (9.83±0.40 mm) was observed in isolate BHSS15, while none showed lipolytic activity. That is the first report on extremophile bacterial isolation and screening for enzyme production from the hot spring in South Sulawesi, Indonesia.